2010
DOI: 10.1176/jnp.2010.22.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Stroke: Plasticity, Vulnerability, and Age of Lesion Onset

Abstract: The authors aim to investigate brain plasticity and vulnerability through the study of the relationship of age at the time of brain injury and neurocognitive and psychiatric outcome. Children with early stroke performed more poorly compared with children with late stroke in a wide variety of domains including intellectual function, language, memory, visuospatial function, academic function, and psychiatric problems. The exception to this pattern was that children with late stroke performed more poorly in two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 41 publications
2
51
1
2
Order By: Relevance
“…Age at stroke onset was not associated with ADHD traits in children with stroke [24,23].However, the early onset stroke group had lower CGAS scores when compared to the later onset group. They also had a higher severity and a higher mean number of psychiatric disorders [25].…”
Section: Factors Associated With Psychosocial Outcomementioning
confidence: 98%
See 2 more Smart Citations
“…Age at stroke onset was not associated with ADHD traits in children with stroke [24,23].However, the early onset stroke group had lower CGAS scores when compared to the later onset group. They also had a higher severity and a higher mean number of psychiatric disorders [25].…”
Section: Factors Associated With Psychosocial Outcomementioning
confidence: 98%
“…Twenty-six studies did not recruit a control group but compared scores to published normative population data. Of the remaining ten that did recruit control participants, these included typically developing children as controls [20,8,21]; children with other non-neurological health conditions, such as orthopaedic and chronic asthma controls [22,23,24,25,26,21,8]; and some children with other neurodevelopmental conditions but without stroke, such as sickle cell disease controls [27] or malformations of cortical development [28]. The participant sample sizes in the studies ranged from fourteen children [28] to 163 children [2].…”
Section: Insert Figure 1 About Herementioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable evidence that an early brain insult is associated with a broad spectrum of neuropsychological dysfunction [57,58]. In fact, the onset of stroke at a younger age predisposes to an overall worse prognosis [59][60][61], weaker cognitive performance, and is subject to lesion location [62]. Westmacott et al [62] reported that individuals who suffered a subcortical stroke (affecting the thalamus and/or basal ganglia axis) before the age of 28 days performed significantly poorer in terms of intellectual performance than older children with the same insult.…”
Section: Predictors Of Long-term Neurodevelopmen-tal Outcome Followinmentioning
confidence: 99%
“…We hypothesized that age at capture would influence the susceptibility of striped mice to SB development for two interrelated reasons. First, social and physical deprivation early in life is known to affect an organism's brain and behavioural development more adversely than deprivation later in life (Max et al 2010) and, second, an increased duration of exposure to environmental complexity is thought to confer greater and more lasting protection against later adversity (Nithianantharajah & Hannan 2006;cf. Lewis et al 2006).…”
Section: Experiments 3: Age At Capturementioning
confidence: 99%